Oral Candida spp. Density as a Blood Glucose Marker in Diabetes Mellitus Patients - Insana, Aima; Nurlailah, Nurlailah; Adawiyah, Rabiatul (Baiman Bauntung Batuah Center, 2025)
Candida spp. is a commensal fungus in the oral cavity that can become an opportunistic pathogen when there is a decrease in the immune system or metabolic disorders such as diabetes mellitus. Hyperglycemia in people with diabetes increases salivary glucose levels, which can be a nutrient source for Candida, thus triggering increased density, biofilm formation, and antifungal resistance. This study aims to analyse the relationship between blood glucose levels and oral Candida spp. density in patients with diabetes mellitus. The study used a cross-sectional design in 29 Guntung Manggis Banjarbaru Community Health Centre patients. Saliva samples were collected by mouthwash and planted on Hichrome Candida Differential Agar (HCDA) media to calculate colony density. At the same time, blood glucose levels were measured spectrophotometrically using the GOD-PAP method. The results showed abnormal blood glucose levels (?200 mg/dL) were found in 16 respondents (55.2%), and abnormal Candida spp. density (>500 CFU/mL) was also found in 16 respondents (55.2%). The growth of Candida spp. detected in 24 samples (82.8%). The Chi-square test showed a significant association between hyperglycemia and increased oral Candida spp. density (p = 0.017). These findings suggest that hyperglycemia plays a role in increased Candida density in the oral cavity. Hence, monitoring blood glucose levels and oral Candida density is important for preventing fungal infection complications in patients with diabetes mellitus.